Tell Hadidi and Energy Dispersive X-Ray Fluorescence Analysis: Are There Ceramic Geochemical Signatures? - (:unkn) unknown (My University, 2020)
X-ray fluorescence (XRF) analysis using a portable analyzer is a non-destructive technology with the potential to answer many questions about ancient ceramics. This paper presents the results of a preliminary study on a portion of the Area C ceramics from Tell Hadidi (Syria) designed to test this technology. Two avenues of inquiry were investigated: could the ceramics be grouped by geochemical similarities? Could these groups then be used to identify any possible geosignatures specific to any vessel or form? The challenges involved in determining analytical parameters and procedures will also be briefly discussed.